COMMUNICATIVE TESTING IN THE EFL CLASSROOM - Hull, Todd (PUPIL: International Journal of Teaching, Education and Learning, 2019)
While the communicative approach has come to predominate in EFL classrooms around the world, its logical corollary—communicative testing—has not followed suit as it seems it should have. Instead, teachers who use the communicative approach in their regular classes often revert to older styles of testing when it comes time for midterms and finals. This paper will define what a communicative test is and why it is a better option than older forms of testing—especially in communicative classrooms, where it is a natural partner. It will then discuss how to assess communicative tests. It will also discuss how communicative testing can be a part of a variety of learning environments Finally, it will give concrete examples of communicative tests that can be used in EFL classrooms from English for Specific Purposes to Content-based Instruction—and even in classrooms that are constrained by administrative mandates so as not to be primarily communicative—demonstrating that communicative testing can be profitably administered in almost any learning environment.